Beyond the Cosmopolis: Sustaining Hyper-Diversity in the Suburbs of Peel Region, Ontario - Dean, Jennifer (2018)
Globalization has increased the flow of transnational migrants into many European and North American cities. These shifting socio-demographic patterns have resulted in the rapid development of ‘cosmopolitan’ urban centres where difference and diversity are ubiquitous (Sandercock, 2003). However, as ethnic enclaves form outside the urban core in suburban communities, there is uncertainty about whether cultural homogeneity is desirable or sustainable in a multicultural country. Indeed, planning communities for increasing diversity and difference will remain, what Leonie Sandercock (2004) calls, “one of the greatest tasks for planners of the 21st century”. Thus, this article uses the theory of hyper-diversity to illuminate how immigrants’ interactions with their local suburban community represents cultural pluralism and diversity beyond ethnicity. Specifically, this study explores differing attitudes, activities and lifestyles among diverse immigrant populations in the Region of Peel, one of the fastest growing and most culturally diverse areas in Canada. Focus groups with 60 immigrant youth and 55 immigrant adults were conducted to qualitatively capture perspectives and experiences in ethnic enclaves. The findings highlight the existence of attitudes in favor of multicultural lifestyles, activities that take newcomers beyond the borders of their enclaves, and lifestyles that require additional infrastructure to support sustainability of immigration in the suburbs. In conclusion, this article adds to the debate on cultural pluralism and ‘homogeneous’ ethnic enclaves by using the emergent concept of hyper-diversity as a way to think about the future sustainability of suburbs in an era of global migration.